Recovery of valuable metals from anode material of hydrogen-nickel battery - 吴芳 徐盛明 李林艳 陈崧哲 徐刚 徐景明 (Transactions of Nonferrous Metals Society of China, 2009)
Simultaneous recovery of rare earth, nickel and cobalt resources from the anode material of hydrogen-nickel battery was performed through a hydrometallurgical process. Most of rare earth elements are separated from nickel and cobalt in the form of sulfates when the anode material is firstly leached with sulfuric acid. Then, the precipitated rare earth sulfates are dissolved with sodium hydroxide to form rare earth hydroxides. The rare earth element, zinc and manganese ions in the lixivium are also separated from nickel and cobalt by using PC-88A extractant system, and the organic phase loaded rare earth is stripped with hydrochloric acid. By neutralizing the stripping solution with rare earth hydroxide, the rare earth chloride is obtained. Under the suitable leaching conditions of sulfuric acid 3 mol/L, leaching time 4 h and temperature 95 ℃, 94.5% of rare earth in the anode material is transformed into the sulfate precipitates, and the leaching ratios of nickel and cobalt can approach 99.5%. When the pH value of the extractive system is controlled in the range of 3.0-3.5, the rare earth elements in the lixivium can be extracted completely into the organic phase, and the stripping recovery of the rare earth can reach 98% in the extraction stage. The total recoveries of rare earth, nickel and cobalt are 98.9%, 98.4% and 98.5%, respectively.